2021
DOI: 10.3390/brainsci11101270
|View full text |Cite
|
Sign up to set email alerts
|

Thalamus Atrophy in the Peri-Pregnancy Period in Clinically Stable Multiple Sclerosis Patients: Preliminary Results

Abstract: Radiological activity in the post-partum period in MS patients is a well-known phenomenon, but there is no data concerning the influence of pregnancy on regional brain atrophy. The aim of this article was to investigate local brain atrophy in the peri-pregnancy period (PPP) in patients with MS. Thalamic volume (TV); corpus callosum volume (CCV) and classical MRI activity (new gadolinium enhancing lesions (Gd+), new T2 lesions, T1 lesions volume (T1LV) and T2 lesions volume (T2LV)) were analyzed in 12 clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Brain and spinal cord atrophy are considered as hallmarks of neurodegeneration in MS [8][9][10]. Both white and grey matter volume loss as well as local atrophy of particular brain structures (e.g., thalamus) have been repeatedly demonstrated as strong correlates of physical and cognitive disability progression in MS [11][12][13][14]. However, little is known about brain atrophy in SDCNS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Brain and spinal cord atrophy are considered as hallmarks of neurodegeneration in MS [8][9][10]. Both white and grey matter volume loss as well as local atrophy of particular brain structures (e.g., thalamus) have been repeatedly demonstrated as strong correlates of physical and cognitive disability progression in MS [11][12][13][14]. However, little is known about brain atrophy in SDCNS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, little is known about the effect of pregnancy on radiological disease activity. Some studies have reported an increased occurrence of new or contrast‐enhancing lesions on brain magnetic resonance imaging (MRI) early after delivery [9,13–17]. On the other hand, to date only two studies have investigated brain volume loss (BVL) after pregnancy, and showed either an absence of accelerated BVL [13] or thalamic but not corpus callosum volume reduction [17], despite an increase in lesion burden.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported an increased occurrence of new or contrast‐enhancing lesions on brain magnetic resonance imaging (MRI) early after delivery [9,13–17]. On the other hand, to date only two studies have investigated brain volume loss (BVL) after pregnancy, and showed either an absence of accelerated BVL [13] or thalamic but not corpus callosum volume reduction [17], despite an increase in lesion burden. In contrast, a few studies on healthy women showed substantial BVL during pregnancy [18–21], with a reduction beginning in early pregnancy and culminating at delivery [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations